A Rapid Method for Quantifying RNA and Phytohormones From a Small Amount of Plant Tissue - Cao, Da; Barbier, Francois; Yoneyama, Kaori; Beveridge, Christine A. (Frontiers in Plant Science, 2020)
Phytohormones are involved in most plant physiological processes and the quantification of endogenous phytohormone levels and related gene expressions is an important approach to studying phytohormone functions. However, the quantification of phytohormones is still challenging due to their extremely low endogenous level in plant tissues and their high chemical diversity. Therefore, developing a method to simultaneously quantify phytohormone levels and RNA would strongly facilitate comparative analyses of phytohormones and gene expression. The present work reports a convenient extraction protocol enabling multivariate analysis of phytohormones and RNA from small amounts of plant material (around 10 mg). This high-throughput ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method demonstrates quantification of phytohormones and their related metabolites from four plant hormone classes: cytokinin, auxin, abscisic acid, and gibberellin. The UPLC-MS/MS method can quantify thirteen phytohormones and their metabolites simultaneously in 14 min. To validate the developed method, we determined the dynamic profiles of phytohormones and gene expressions in small axillary shoot buds in garden pea. This new method is applicable to quantification analysis of gene expression and multiple phytohormone classes in small amounts of plant materials. The results obtained using this method in axillary buds provide a basis for understanding the phytohormone functions in shoot branching regulation.